Film theory and philosophy - Allen, Richard, 1959-; Smith, Murray, 1962- (Clarendon, 1997)
This volume is comprised of new essays on a wide range of topics by both film scholars and philosophers who share the commitment to conceptual investigation, logic consistency, and clarity of argument and characterizes analytic philosophy.